A NEW STRATOSPHERE? INVESTMENT TREATY ARBITRATION AS 'INTERNATIONALIZED PUBLIC LAW'. Issue 2 (30th April 2015) - Unknown
Abstract: The idea of investment treaty arbitration as public law is in tension with the concept of international law as a law between representative public agencies. This concept of international law is valuable for its capacity to progress a broad range of public policy aims in an integrated and coordinated manner, including aims extending beyond the economic sphere such as international social, environmental, cultural and related aims. The probable effect on this concept of international law of a radical 'internationalized public law' approach to investment treaty arbitration requires further thought, especially with regard to the potential implications of recognizing investor rights under international law.